Designing SDGs-Oriented Digital Materials to Foster 21st Century Learning in the Productive Written Language Skill Course - Br. Batubara, Khairunnisa; Erlita, Yeni; Oktora, Maya; Frida, Karunia Devi; Khairina, Yuni; Natalia, Christine Helena; Dewi, Nora Ronita (Jambura Journal of English Teaching and Literature, 2025)
This study aims to design and evaluate SDG-oriented digital learning materials for the Productive Written Language Skill (PWLS) course in alignment with 21st-century learning principles. Responding to the growing need to integrate global citizenship and sustainability into English language education, the materials embed Sustainable Development Goals (SDGs) within argumentative writing tasks. A research and development (R&D) approach (Branch, 2010) was employed, involving expert validation, student testing, and classroom observation. Two subject-matter experts assessed the materials and rated them as very good (M = 4.0) in terms of relevance, clarity, and integration of SDG content. Thirty students from the English Education Study Program at Universitas Negeri Medan participated in the implementation stage. Their feedback indicated strong engagement and perceived usefulness (M = 4.16), while pre- and post-test results showed significant improvement in writing performance—from 65.30 to 76.40. Observational data confirmed high student participation and timely task completion, with only minor navigation issues. Overall, the SDG-oriented digital modules effectively supported language development, critical thinking, and 21st-century competencies. The findings imply that SDG-oriented digital materials can effectively foster students’ critical thinking and writing competence in the Productive Written Language Skill course, supporting the goals of 21st-century learning.